IMPROVING THE TEACHING AND LEARNING QUALITY BY DEVELOPING AUN-QA BASED COURSE OUTLINES - Suharmanto, Suharmanto,; Maria Hidayati; Evynurul Laily Zen (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
The primary purpose of this article is to provide detailed process in develop- ing AUN-QA based course outlines as a way to improve the quality of teaching and learning. AUN-QA which stands for ASEAN University Network Quality Assurance is selected due to its recognition of raising academic standards and enhancing education, research and service among AUN university members (AUN-QA guideline, 2010). It is a research and development study which is conducted through the following stages: (1) research and information collecting from AUN-QA guideline, the teaching and learning present condition of English Department, State University of Malang and the course outline models; (2) planning the arrangement of questionnaire items and its distribution to students; (3) developing AUN-QA course outlines; (4) validating the products by AUN- QA and curriculum experts; and (5) trying out the products to the students.